Rejuvenation and Characterization of Local Rice Germplasm (Orya sativa L.) Under Organic Cultivation Syste - . Efendi; . Bakhtiar; Sabaruddin Zakaria; . Syafruddin (Syiah Kuala University, 2015)
The research was carried out to rejuvenate and evaluate the performances of plant characters of rice genotyps to produce a pure lines that are suitable for organic cultivation method. Thirty genotypes of the selected local rice were conducted to evaluate the phenotype performances under the organic cultivation method. The rice genotypes were utilized in this experiment to evaluate their morpho-agronomic characters under organic cultivation system. Characterization of seed performances of each accession was described and catalogued to identify their accession traits. In addition, genotypic differences and similarities were also characterized and catalogued. Duplicate accessions were eliminated from the same variety or nearly identical variants of a variety. The morpho-agronomic performances of plant height, number of tillers, lifespan, number of panicles, filled grains per spike, 1000 grains weight, grain yield potential, and harvest index were clearly affected by the genotype. The results showed that the genotypes were greatly varied the morphoagronomic performances. , if organic system was applied, it was found that the responses of rice growth and yield of local varieties of Aceh is better than rice varieties cultivated by the national and introduction genotype.